Community Service Machinery Maintenance Training in Tossa - Katsiro, Hamdan; Shofian, Riza Muhammad; Maulana, David; Azizi, Ferdian Tegar Al; Arto, Rega Andreawan Ari Wahyudi; Ridlo, Muhammad Zainur (Journal Of Humanities Community Empowerment, 2025)
Three-wheeled vehicles such as Tossa play a vital role in supporting community economic activities, particularly among small-scale entrepreneurs. However, limited technical knowledge among users often leads to machine performance degradation and increased risk of damage. This community service program aimed to enhance students’ understanding and skills in basic Tossa engine maintenance. The one-day training was attended by 10 Mechanical Engineering students from Universitas Muhammadiyah Jember. The method involved lectures, hands-on practice, discussion, and kuiszes for evaluation. Results revealed that 80% of participants were able to adjust the carburetor and clean the air filter independently, while all participants successfully performed oil changes and spark plug cleaning. This activity proved effective in improving participants’ technical competencies and serves as an initial step towards fostering entrepreneurship based on practical automotive skills..